The Role of Social Management In Oil Palm Land Conservation In Preventing Land Conversion In Bumi Raya District, Morowali Regency, Central Sulawesi, Indonesia - Idham Idham; Mohammad Yasin; Abdul Wahab (International Journal Of Community Service, 2026)
The Role of Social Management, Oil Palm Land Conservation, and Land Conversion Prevention in Bumi Raya District, Morowali Regency, Central Sulawesi. This study analyzes the role of social management in oil palm land conservation efforts to prevent continued land conversion, resulting in a decreasing area of ​​productive oil palm land, which occurs in Bumi Raya District, Morowali Regency, Central Sulawesi. The study aims to identify effective social management strategies, examine supporting, inhibiting, and successful factors, and recommend appropriate policies, efforts to increase community participation, and maintain the sustainability of oil palm land. The research method used is a qualitative case study approach, namely a single case, data collection techniques in the form of interviews, observations, and documentation studies. The results of the study indicate that social management plays an important role in the success of land conservation and preventing land conversion, success is influenced by several factors, such as community participation, government support, and access to information and technology. The study recommends increasing community capacity through training and counseling, strengthening community institutions for managing land to become economically valuable, and reducing oil palm land conversion in Bumi Raya District. In conclusion, sustainable participatory social management by local communities is key to the success of oil palm land conservation efforts and the prevention of land conversion in Bumi Raya District, Morowali Regency.